Photovoltaic tempered glass and preparation method thereof

By using the collaborative technology of fluoropolysiloxane and silica/tetra-acid zinc oxide whiskers/alkyl phosphate, titanium dioxide/polymer molecular brush on the surface of the photovoltaic tempered glass, the problem of the lower adhesion of photovoltaic tempered glass after high temperature and high humidity and high temperature impact treatment is solved, and the effects of superhydrophobic, self-cleaning, ultraviolet resistance and high light transmittance are achieved.

CN119592219AInactive Publication Date: 2025-03-11GUANGDONG SENYUXIN PHOTOVOLTAIC MATERIALS CO LTD

Patent Information

Application Number
CN202411918818.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The adhesion of existing photovoltaic tempered glass decreases after high temperature, high humidity and high temperature impact treatment, and fails to reach the superhydrophobic state.

Method used

The hydroxyl group is introduced at both ends of the siloxane through ring-opening polymerization, and the fluorine-element is introduced into the side chain to form fluorine-containing polysiloxane and the surface of the tempered glass is condensed to improve adhesion. Meanwhile, the synergistic effect of silica/tetra-acid zinc oxide whiskers/alkyl phosphate and titanium dioxide/polymer molecular brushes imparted the superhydrophobic state to the coating.

Benefits of technology

It improves the adhesion of the coating after high temperature, high humidity and high temperature impact treatment, and achieves a superhydrophobic state, with excellent self-cleaning, ultraviolet resistance and light transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207453610000101
    Figure BDA0005207453610000101
  • Figure BDA0005207453610000111
    Figure BDA0005207453610000111
Patent Text Reader

Abstract

The invention belongs to the technical field of photovoltaic tempered glass, and particularly relates to photovoltaic tempered glass and a preparation method thereof.The photovoltaic tempered glass sequentially comprises tempered glass and a protective coating from bottom to top; the protective coating is prepared from the following raw materials in parts by mass: 20 to 45 parts of fluorine-containing polysiloxane, 10 to 18 parts of tetraethoxysilane, 10 to 20 parts of silicon dioxide / tetrapod-like zinc oxide whisker / alkyl phosphate, 10 to 20 parts of titanium dioxide / polymer molecular brush, 0.5 to 1 part of catalyst and 80 to 120 parts of solvent; the fluorine-containing polysiloxane is obtained by carrying out a reaction on octamethyl cyclotetrasiloxane, decamethyl cyclopentasiloxane and trifluoropropyl methyl cyclotrisiloxane. The photovoltaic tempered glass provided by the invention has super-hydrophobicity, excellent light transmittance, high-temperature and high-humidity resistance, high and low temperature impact resistance and ultraviolet resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photovoltaic tempered glass, and in particular relates to photovoltaic tempered glass and a preparation method thereof. Background Art

[0002] Photovoltaic tempered glass is a special glass designed for solar photovoltaic modules. It plays a vital role in photovoltaic systems. Photovoltaic tempered glass can not only protect the internal photovoltaic cells from external environmental factors, such as wind, sand, hail and other physical damage, but also ensure the maximum transmission of sunlight, thereby improving the energy conversion efficiency of photovoltaic modules.

[0003] In order to improve the light transmittance of photovoltaic tempered glass, reduce reflection loss, provide self-cleaning function and enhance weather resistance, one or more functional coatings are usually applied to the surface of photovoltaic tempered glass. For example, the Chinese patent with the authorization publication number CN107163783B in the prior art discloses a photovoltaic glass panel surface layer anti-attenuation coating and its preparation method. The photovoltaic glass panel surface layer anti-attenuation coating includes the following raw materials in weight percentage: 8%-20% fluorosilicone copolymer resin, 5%-12% silicon dioxide, 2%-8% dispersant, 1%-5% penetrant, 0.5%-2% defoamer, 1.5%-5% leveling agent, and the balance is diluent. The photovoltaic glass panel surface layer anti-attenuation coating of the technical solution has a hydrophobicity of 95%, a large contact angle with water, reaching more than 130°, and a rolling angle of less than 20°, so it has good self-cleaning ability under the scouring of rainwater, and at the same time, the light transmittance reaches more than 98%, and the photovoltaic conversion rate can be guaranteed while having a self-cleaning effect. However, although the above performance is very close to the standard of super hydrophobic surface, that is, the static contact angle is greater than 150° and the rolling angle is less than 10°, the technical solution has not reached the "super hydrophobic" state.

[0004] A Chinese patent with publication number CN117777847A discloses a self-cleaning photovoltaic glass coating and a preparation method thereof. The self-cleaning photovoltaic glass coating is prepared from raw materials including the following percentages: 2% to 4% nano titanium dioxide, 3% to 6% nano silicon dioxide, 10% to 20% water-based silicone modified acrylic resin, 20% to 30% water-based silicone resin, 0.5% to 2% sodium polymethacrylate, 4% to 8% polypropylene glycol, 2% to 3% nonylphenol polyoxyethylene ether, 1% to 2% defoaming agent, 1% to 3% ethylene glycol, and the balance is water; the technical solution forms a surface coating on the surface of the photovoltaic glass by spraying the photovoltaic glass coating on the surface of the photovoltaic glass. The surface coating has a smooth surface and excellent antistatic and hydrophilic properties, can effectively avoid the accumulation of dust particles and is easy to remove dust particles when it rains or is flushed with water. In addition, the surface coating has excellent light transmittance and weather resistance. However, this technical solution is a water-based coating, and the weather resistance of the formed coating may decrease when it is exposed to ultraviolet rays, rain and other environments for a long time. Summary of the invention

[0005] In view of the above problems, the present invention provides a photovoltaic tempered glass and a preparation method thereof. The photovoltaic tempered glass provided by the present invention has super hydrophobicity, excellent light transmittance, high temperature and humidity resistance, high and low temperature impact resistance and UV resistance.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] The first aspect of the present invention provides a photovoltaic tempered glass, which comprises tempered glass and a protective coating in order from bottom to top; the raw materials of the protective coating, by weight, comprise: 20-45 parts of fluorine-containing polysiloxane, 10-18 parts of tetraethyl orthosilicate, 10-20 parts of silicon dioxide / tetra-needle zinc oxide whisker / alkyl phosphate, 10-20 parts of titanium dioxide / polymer molecular brush, 0.5-1 part of catalyst, and 80-120 parts of solvent; the fluorine-containing polysiloxane is obtained by reacting octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and trifluoropropylmethylcyclotrisiloxane.

[0008] In some preferred embodiments, the preparation method of the fluorinated polysiloxane comprises the following steps: under a nitrogen protective atmosphere, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and trifluoropropylmethylcyclotrisiloxane are uniformly mixed, stirred for reaction, tetramethylammonium hydroxide aqueous solution and water are added to continue stirring for reaction, the pressure is reduced, and the reaction is continued to obtain the fluorinated polysiloxane.

[0009] In some preferred embodiments, the mass ratio of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and trifluoropropylmethylcyclotrisiloxane is (1-2):(1.5-2):(3-5), preferably 1.5:1.8:4.

[0010] Fluorinated polysiloxane can reduce surface energy and improve the hydrophobicity of the coating. However, the inventors have found that although the fluorinated polysiloxane obtained by modifying the organic siloxane with perfluorooctyl triethoxysilane or tridecafluorooctyl trimethoxysilane significantly improves the hydrophobicity of the coating, its adhesion after high temperature and humidity and high and low temperature impact treatment is significantly reduced. In order to solve this technical problem, the present invention uses methyl cyclotetrasiloxane, decamethyl cyclopentasiloxane and trifluoropropyl methyl cyclotrisiloxane to introduce hydroxyl groups at both ends of the siloxane through ring-opening polymerization, and introduces fluorine elements on the side chain. The hydroxyl groups at both ends of the obtained fluorinated polysiloxane can undergo condensation reaction with the silanol groups existing on the surface of the tempered glass to generate more stable siloxane bonds or form hydrogen bonds with the surface of the tempered glass, thereby improving the adhesion of the coating after high temperature and humidity and high and low temperature impact treatment.

[0011] However, the ability of fluorinated silicone to improve the hydrophobicity of the coating is poor, and the resulting coating cannot reach a super-hydrophobic state. Based on this, it is necessary to add fillers in order to construct a rough structure to achieve a super-hydrophobic state. The inventors prepared silica / tetra-needle-shaped zinc oxide whiskers / alkyl phosphates and titanium dioxide / polymer molecular brushes based on tetra-needle-shaped zinc oxide whiskers and titanium dioxide through a large number of creative experiments, and found that the two can synergistically impart a super-hydrophobic state to the coating, thereby achieving self-cleaning of the coating. At the same time, the inventors also found that the coating has excellent UV resistance.

[0012] During the experiment, the inventors found that directly adding alkyl phosphate-modified tetrapodal zinc oxide whiskers into the system would reduce the adhesion of the coating after high and low temperature impact, while silica / tetrapodal zinc oxide whiskers / alkyl phosphate could avoid this problem. It is speculated that this is because silica can fill the gaps in the tetrapodal zinc oxide whiskers, further improving the roughness of the coating. At the same time, the silica protrusions on the surface of the tetrapodal zinc oxide whiskers can form an anchoring effect with the fluorinated polysiloxane, thereby toughening the coating.

[0013] The inventors also found that although the addition of silica / tetrapod-shaped zinc oxide whiskers / alkyl phosphates can increase the water contact angle of the coating, its water rolling angle also increases, and a superhydrophobic state cannot be achieved. The inventors unexpectedly discovered that grafting a polymer molecular brush composed of a quaternary ammonium salt of organic silicon and polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt on the surface of titanium dioxide not only improves the UV resistance of the coating, but also avoids the increase in the water rolling angle and the transmittance of the photovoltaic tempered glass. It is speculated that this is because the polymer molecular brush formed on the surface of titanium dioxide can act as an intermediate layer and has a fluid lubrication effect, thereby avoiding the increase in the water rolling angle, while reducing the refractive index mutation at the interface between the coating and the tempered glass, reducing light scattering, and avoiding a decrease in the transmittance of the photovoltaic tempered glass.

[0014] In some preferred embodiments, the concentration of the tetramethylammonium hydroxide aqueous solution is 20-25 wt %.

[0015] In some preferred embodiments, the mass ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide aqueous solution and water is 10:(0.002-0.004):(0.03-0.04).

[0016] In some preferred embodiments, the preparation method of the fluorinated polysiloxane comprises the following steps: under a nitrogen protective atmosphere, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and trifluoropropylmethylcyclotrisiloxane are uniformly mixed, stirred and reacted at 80-90° C. for 30-40 min, heated to 110-120° C., tetramethylammonium hydroxide aqueous solution and water are added, and the stirring reaction is continued for 3-4 h, heated to 150° C., and the stirring reaction is continued for 3-4 h, and the pressure is reduced to 2-2.5 KPa, and the reaction is continued for 3-4 h to obtain the fluorinated polysiloxane.

[0017] Further preferably, the preparation method of the fluorinated polysiloxane comprises the following steps: under a nitrogen protective atmosphere, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and trifluoropropylmethylcyclotrisiloxane are uniformly mixed, stirred and reacted at 85° C. for 35 minutes, heated to 115° C., tetramethylammonium hydroxide aqueous solution and water are added, and the stirring reaction is continued for 3.5 hours, heated to 150° C., and the stirring reaction is continued for 3.5 hours, the pressure is reduced to 2.2 KPa, and the reaction is continued for 3.5 hours to obtain the fluorinated polysiloxane.

[0018] In some preferred embodiments, the method for preparing the silicon dioxide / tetrapod-shaped zinc oxide whisker / alkyl phosphate comprises the following steps:

[0019] (1) uniformly mixing tetrapod-shaped zinc oxide whiskers and ethanol aqueous solution, dropwise adding ammonia water and ethyl orthosilicate, ultrasonically reacting, washing, filtering, and drying to obtain silicon dioxide / tetrapod-shaped zinc oxide whiskers;

[0020] (2) mixing silica / tetrapod-shaped zinc oxide whiskers and alkyl phosphate salt solution uniformly, subjecting to ultrasonic reaction, washing, filtering and drying to obtain silica / tetrapod-shaped zinc oxide whiskers / alkyl phosphate.

[0021] In some preferred embodiments, the mass ratio of the tetrapod-shaped zinc oxide whiskers, ethanol aqueous solution, ammonia water and tetraethyl orthosilicate in step (1) is 1:(20-30):(1-1.2):(0.9-1.2), preferably 1:25:1.1:1.

[0022] In some preferred embodiments, the temperature of the ultrasonic reaction in step (1) is 25-30° C., and the time of the ultrasonic reaction is 4-8 h.

[0023] In some preferred embodiments, the alkyl phosphate salt solution in step (2) is an aqueous solution of potassium dodecyl phosphate with a concentration of 1 g / L.

[0024] In some preferred embodiments, the mass ratio of silicon dioxide / tetrapod-shaped zinc oxide whiskers to alkyl phosphate salt solution in step (2) is 1:(30-40), preferably 1:35.

[0025] In some preferred embodiments, the temperature of the ultrasonic reaction in step (2) is 25-30° C., and the time of the ultrasonic reaction is 2-3 h.

[0026] In some preferred embodiments, the method for preparing the titanium dioxide / polymer molecular brush comprises the following steps:

[0027] S1, mixing nano titanium dioxide, polyol and ethanol aqueous solution uniformly, ultrasonically treating, washing, filtering and drying to obtain a nano titanium dioxide / polyol composite;

[0028] S2, mixing the nano titanium dioxide / polyhydroxy compound complex, organosilicon quaternary ammonium salt, and ethanol aqueous solution, adjusting the pH to 3-4, ultrasonically treating, washing, filtering, and drying to obtain the nano titanium dioxide / polyhydroxy compound / organosilicon quaternary ammonium salt complex;

[0029] S3, mixing nano titanium dioxide / polyhydroxy compound / organosilicon quaternary ammonium salt complex, polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt and chloroform evenly, reacting, washing, filtering and drying to obtain titanium dioxide / polymer molecular brush.

[0030] In some preferred embodiments, the polyhydroxy compound is at least one of tannic acid and ferulic acid, preferably tannic acid.

[0031] In some preferred embodiments, the mass ratio of nano-titanium dioxide, polyhydroxy compound and ethanol aqueous solution in step S1 is 1:(4-6):(15-25), preferably 1:5:20.

[0032] In some preferred embodiments, the temperature of the ultrasonic treatment in step S1 is 25-30° C., and the time of the ultrasonic treatment is 30-60 min.

[0033] In some preferred embodiments, the particle size of the nano-titanium dioxide in step S1 is 10-40 nm, preferably 20 nm.

[0034] In some preferred embodiments, the organosilicon quaternary ammonium salt in step S2 is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.

[0035] In some preferred embodiments, the mass ratio of the nano-titanium dioxide / polyhydroxy compound composite, the organosilicon quaternary ammonium salt, and the ethanol aqueous solution in step S2 is 1:(0.4-0.6):(15-25), preferably 1:0.5:20.

[0036] In some preferred embodiments, the temperature of the ultrasonic treatment in step S2 is 25-30° C., and the time of the ultrasonic treatment is 30-60 min.

[0037] In some preferred embodiments, in step S3, the mass ratio of nano-titanium dioxide / polyhydroxy compound / organosilicon quaternary ammonium salt complex, polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt, and chloroform is 1:(1.5-2):(10-20), preferably 1:1.8:15.

[0038] In some preferred embodiments, the reaction temperature in step S3 is 60-70° C., and the reaction time is 8-12 h.

[0039] In some preferred embodiments, the concentration of the ethanol aqueous solution involved in the present invention is 95 vol%.

[0040] In some preferred embodiments, the catalyst is an aqueous hydrochloric acid solution; the concentration of the aqueous hydrochloric acid solution is 2 mol / L.

[0041] In some preferred embodiments, the organic solvent is selected from at least one of ethanol, isopropanol and methanol.

[0042] In some preferred embodiments, the protective coating has a thickness of 3-5 μm.

[0043] The second aspect of the present invention provides a method for preparing the above-mentioned photovoltaic tempered glass, comprising the following steps: mixing and stirring ethyl orthosilicate and a solvent, adding a catalyst during the stirring process, adjusting the pH to 4.5, standing and aging to obtain a silica sol; mixing and stirring the silica sol, a fluorinated polysiloxane, a polyborosilazane, silicon dioxide / tetra-needle zinc oxide whisker / alkyl phosphate, and titanium dioxide / polymer molecular brushes to obtain a protective coating; applying the protective coating on the surface of the tempered glass, and curing to obtain the photovoltaic tempered glass.

[0044] Preferably, the curing temperature is 60-120° C. and the curing time is 2-7 hours.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1. The present invention uses methylcyclotetrasiloxane, decamethylcyclopentasiloxane and trifluoropropylmethylcyclotrisiloxane to introduce hydroxyl groups at both ends of siloxane through ring-opening polymerization, and introduces fluorine element on the side chain. The hydroxyl groups at both ends of the obtained fluorinated polysiloxane can undergo condensation reaction with the silanol groups existing on the surface of tempered glass to generate more stable silicon-oxygen bonds or form hydrogen bonds with the surface of tempered glass, thereby improving the adhesion of the coating after high temperature and high humidity and high and low temperature impact treatment.

[0047] 2. The present invention uses silicon dioxide / tetrapod-shaped zinc oxide whiskers / alkyl phosphates and titanium dioxide / polymer molecular brushes, which can synergistically impart a superhydrophobic state to the coating, thereby achieving self-cleaning of the coating. At the same time, the coating has excellent UV resistance.

[0048] 3. The silicon dioxide / tetrapod-shaped zinc oxide whisker / alkyl phosphate of the present invention can prevent the adhesion of the coating from decreasing after high and low temperature impact.

[0049] 4. The titanium dioxide surface of the present invention is grafted with a polymer molecular brush composed of organosilicon quaternary ammonium salt and polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt, which not only improves the UV resistance of the coating, but also avoids the increase of the water rolling angle and improves the transparency of the tempered glass. DETAILED DESCRIPTION

[0050] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, a specific implementation scheme is now described in detail.

[0051] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to the different requirements of specific use, and the implementation conditions not indicated are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0052] In the following examples and comparative examples, unless otherwise specified, all raw materials used were commercially available or prepared by conventional methods in the art.

[0053] The concentration of the ethanol aqueous solution in the following examples and comparative examples is 95 vol%; the photovoltaic tempered glass is purchased from Rainbow Group New Energy Co., Ltd., with a thickness of 2.5 mm; and the light transmittance is ≥93.7%.

[0054] Example 1

[0055] A photovoltaic tempered glass comprises, from bottom to top, a tempered glass and a protective coating; the raw materials of the protective coating are composed, by mass, of 20 parts of fluorine-containing polysiloxane, 10 parts of tetraethyl orthosilicate, 10 parts of silicon dioxide / tetrapod-shaped zinc oxide whiskers / alkyl phosphates, 10 parts of titanium dioxide / polymer molecular brushes, 0.5 parts of a catalyst, and 80 parts of a solvent.

[0056] The preparation method of the fluorinated polysiloxane is as follows: under a nitrogen protective atmosphere, octamethylcyclotetrasiloxane (CAS No.: 556-67-2), decamethylcyclopentasiloxane (CAS No.: 541-02-6) and trifluoropropylmethylcyclotrisiloxane (CAS No.: 2374-14-3) are uniformly mixed, stirred and reacted at 85° C. for 35 minutes, heated to 115° C., tetramethylammonium hydroxide aqueous solution and water are added, stirred and reacted for 3.5 hours, heated to 150° C., stirred and reacted for 3.5 hours, reduced pressure to 2.2 KPa, and reacted for 3.5 hours to obtain the fluorinated polysiloxane.

[0057] The mass ratio of the octamethylcyclotetrasiloxane, the decamethylcyclopentasiloxane and the trifluoropropylmethylcyclotrisiloxane is 1.5:1.8:4.

[0058] The concentration of the tetramethylammonium hydroxide aqueous solution is 20 wt %.

[0059] The mass ratio of the octamethylcyclotetrasiloxane, the tetramethylammonium hydroxide aqueous solution and water is 10:0.003:0.03.

[0060] The preparation method of the silicon dioxide / tetrapod-shaped zinc oxide whisker / alkyl phosphate is as follows:

[0061] (1) mixing tetrapod-shaped zinc oxide whiskers and ethanol aqueous solution uniformly, adding ammonia water and tetraethyl orthosilicate (CAS No.: 78-10-4) dropwise, performing ultrasonic reaction, washing, filtering, and drying to obtain silica / tetrapod-shaped zinc oxide whiskers;

[0062] (2) mixing silica / tetrapod-shaped zinc oxide whiskers and alkyl phosphate salt solution uniformly, subjecting to ultrasonic reaction, washing, filtering and drying to obtain silica / tetrapod-shaped zinc oxide whiskers / alkyl phosphate.

[0063] The mass ratio of the tetrapod-shaped zinc oxide whisker, ethanol aqueous solution, ammonia water and tetraethyl orthosilicate in step (1) is 1:25:1.1:1.

[0064] Tetrapod-shaped zinc oxide whiskers were purchased from Hangzhou Jikang New Materials Co., Ltd. with a diameter of 0.5-5 μm

[0065] The temperature of the ultrasonic reaction in step (1) is 25° C., and the time of the ultrasonic reaction is 6 hours.

[0066] The alkyl phosphate salt solution in step (2) is an aqueous solution of potassium dodecyl phosphate (CAS No.: 739322-78-6) with a concentration of 1 g / L.

[0067] In step (2), the mass ratio of silicon dioxide / tetrapod-shaped zinc oxide whiskers to alkyl phosphate salt solution is 1:35.

[0068] The temperature of the ultrasonic reaction in step (2) is 25° C., and the time of the ultrasonic reaction is 2.5 h.

[0069] The preparation method of the titanium dioxide / polymer molecular brush is as follows:

[0070] S1, mixing nano titanium dioxide, polyol and ethanol aqueous solution uniformly, ultrasonically treating, washing, filtering and drying to obtain a nano titanium dioxide / polyol composite;

[0071] S2, mixing the nano titanium dioxide / polyhydroxy compound composite, organosilicon quaternary ammonium salt, and ethanol aqueous solution, adjusting the pH to 3.5, ultrasonically treating, washing, filtering, and drying to obtain the nano titanium dioxide / polyhydroxy compound / organosilicon quaternary ammonium salt composite;

[0072] S3, mixing nano titanium dioxide / polyhydroxy compound / organosilicon quaternary ammonium salt complex, polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt (CAS No.: 119438-10-7) and chloroform evenly, reacting, washing, filtering and drying to obtain titanium dioxide / polymer molecular brush.

[0073] In step S1, the mass ratio of nano-titanium dioxide, polyhydroxy compound and ethanol aqueous solution is 1:5:20.

[0074] The polyhydroxy compound in step S1 is tannic acid (CAS No.: 1401-55-4).

[0075] The temperature of the ultrasonic treatment in step S1 is 25° C., and the time of the ultrasonic treatment is 40 min.

[0076] The particle size of the nano-titanium dioxide in step S1 is 20 nm, purchased from Nanjing Tianxing New Materials Co., Ltd., model: TTP-R80.

[0077] In step S2, the mass ratio of the nano-titanium dioxide / polyhydroxy compound composite, the organosilicon quaternary ammonium salt, and the ethanol aqueous solution is 1:0.5:20.

[0078] The organosilicon quaternary ammonium salt in step S2 is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (CAS No.: 27668-52-6).

[0079] The temperature of the ultrasonic treatment in step S2 is 25° C., and the time of the ultrasonic treatment is 40 min.

[0080] In step S3, the mass ratio of nano-titanium dioxide / polyhydroxy compound / organosilicon quaternary ammonium salt complex, polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt, and chloroform is 1:1.8:15.

[0081] The reaction temperature in step S3 is 65° C. and the reaction time is 10 h.

[0082] The catalyst is a hydrochloric acid aqueous solution; the concentration of the hydrochloric acid aqueous solution is 2 mol / L.

[0083] The organic solvent is ethanol.

[0084] The preparation method of the above-mentioned photovoltaic tempered glass is as follows: mix and stir ethyl orthosilicate and a solvent, add a catalyst during the stirring process, adjust the pH to 4.5, and let it stand for aging to obtain silica sol; mix and stir the silica sol, fluorinated polysiloxane, silicon dioxide / tetrapod-shaped zinc oxide whisker / alkyl phosphate, and titanium dioxide / polymer molecular brush to obtain a protective coating; apply the protective coating on the surface of the tempered glass, and cure it at 80°C for 5 hours to obtain the photovoltaic tempered glass.

[0085] Example 2

[0086] The difference from Example 1 is that the raw materials of the protective coating, calculated by mass, are composed of 30 parts of fluorinated polysiloxane, 15 parts of tetraethyl orthosilicate, 15 parts of silica / tetrapodial zinc oxide whiskers / alkyl phosphate, 115 parts of titanium dioxide / polymer molecular brushes, 0.7 parts of catalyst, and 100 parts of solvent; the rest are the same.

[0087] The preparation method of the photovoltaic tempered glass is the same as that of Example 1.

[0088] Example 3

[0089] The difference from Example 1 is that the raw materials of the protective coating, calculated by mass, are composed of 45 parts of fluorinated polysiloxane, 18 parts of tetraethyl orthosilicate, 20 parts of silica / tetrapodial zinc oxide whiskers / alkyl phosphate, 20 parts of titanium dioxide / polymer molecular brushes, 1 part of catalyst, and 120 parts of solvent; the rest are the same.

[0090] The preparation method of the above-mentioned photovoltaic tempered glass is the same as that of Example 1.

[0091] Comparative Example 1

[0092] The difference from Example 2 is that the fluorinated polysiloxane is replaced by the hydrophobic agent of Chinese Patent Example 1 with publication number CN 118026541 A, that is, 7 mL of an ethanol solution with a mass fraction of 30% is prepared, and the pH is controlled to be 4-6, 1 g of tridecafluorooctyltrimethoxysilane, 0.3 g of 3-glycidyloxypropyltrimethoxysilane and 0.6 g of vinyltrimethoxysilane are added to the above ethanol solution, stirred evenly, and reacted for 2 hours to obtain a hydrophobic agent; the rest are the same.

[0093] Comparative Example 2

[0094] The difference from Example 2 is that the silicon dioxide / tetrapod-shaped zinc oxide whisker / alkyl phosphate is replaced by an equal mass of tetrapod-shaped zinc oxide whisker / alkyl phosphate, and the preparation method of the tetrapod-shaped zinc oxide whisker / alkyl phosphate is: uniformly mixing the tetrapod-shaped zinc oxide whisker and the alkyl phosphate ester salt solution, ultrasonically reacting, washing, filtering, and drying to obtain the tetrapod-shaped zinc oxide whisker / alkyl phosphate; the mass ratio of the tetrapod-shaped zinc oxide whisker to the alkyl phosphate ester salt solution is 1:35; and the rest are the same.

[0095] Comparative Example 3

[0096] The difference from Example 2 is that the four-needle zinc oxide whiskers are replaced with carbon nanotubes of the same mass, the carbon nanotubes have a diameter of 10-25 nm, purchased from Su Tiannai Technology Co., Ltd., model: FT9000; the rest are the same.

[0097] Comparative Example 4

[0098] The difference from Example 2 is that the titanium dioxide / polymer molecular brush is replaced by an equal mass of nano-titanium dioxide / polyhydroxy compound / organosilicon quaternary ammonium salt complex; the rest are the same.

[0099] Comparative Example 5

[0100] The difference from Example 2 is that the silicon dioxide / tetrapod-shaped zinc oxide whisker / alkyl phosphate is replaced by titanium dioxide / polymer molecular brush of the same mass; the rest is the same.

[0101] Comparative Example 6

[0102] The difference from Example 2 is that the titanium dioxide / polymer molecular brush is replaced by the same mass of silicon dioxide / tetrapod-shaped zinc oxide whisker / alkyl phosphate; the rest are the same.

[0103] Test example:

[0104] The photovoltaic tempered glass prepared in Examples 1-3 and Comparative Examples 1-6 was subjected to the following performance tests:

[0105] 1. Water contact angle and water rolling angle: use a contact angle tester to test;

[0106] 2. Light transmittance: Detected by spectrophotometer;

[0107] 3. Adhesion: Reference standard GB / T9286 2021;

[0108] 4. High temperature and high humidity resistance: Test adhesion after 160h at 60℃ and 90%RH.

[0109] 5. High and low temperature impact resistance: Place at -40℃-100℃ for 1h each, and test the adhesion after 20 cycles.

[0110] 6. UV resistance: Place under the condition of ultraviolet wavelength range of 280-400nm and irradiation intensity of 15kW·h / m, use a spectrophotometer to test the transmittance after 2000h, and calculate the transmittance retention rate, which is transmittance after test / transmittance before test × 100%.

[0111] Table 1 Test results of photovoltaic tempered glass of Examples 1-3 and Comparative Examples 1-6

[0112] Water contact angle / ° Water rolling angle / ° Light transmittance / % Adhesion Example 1 158 8 92.5 Level 0 Example 2 160 7 92.7 Level 0 Example 3 157 6 92.3 Level 0 Comparative Example 1 171 7 92.1 Level 0 Comparative Example 2 148 9 92.4 Level 0 Comparative Example 3 141 10 91.8 Level 1 Comparative Example 4 150 18 88.5 Level 0 Comparative Example 5 128 9 91.2 Level 0 Comparative Example 6 135 20 90.1 Level 0

[0113] Table 2 Test results of photovoltaic tempered glass of Examples 1-3 and Comparative Examples 1-6

[0114]

[0115]

[0116] It can be seen from Table 1 and Table 2 that the photovoltaic tempered glass of Examples 1-3 has excellent superhydrophobicity, light transmittance, adhesion, high temperature and humidity resistance, high and low temperature impact resistance, and UV resistance;

[0117] In Comparative Example 1, the fluorinated polysiloxane is replaced with the hydrophobic agent of Example 1 of Chinese Patent Publication No. CN 118026541 A. Although the hydrophobicity of the obtained photovoltaic tempered glass is improved, the high temperature and humidity resistance and the high and low temperature impact resistance are significantly reduced;

[0118] Comparative Example 2: Silicon dioxide / tetrapod-shaped zinc oxide whisker / alkyl phosphate was replaced with tetrapod-shaped zinc oxide whisker / alkyl phosphate of equal mass. The obtained photovoltaic tempered glass had good hydrophobicity, but could not achieve super hydrophobicity, and its high and low temperature impact resistance was significantly reduced, and its UV resistance was also reduced.

[0119] In Comparative Example 3, the four-needle zinc oxide whiskers were replaced with carbon nanotubes of equal mass, and the obtained photovoltaic tempered glass could not achieve super-hydrophobicity, and the adhesion, high temperature and humidity resistance, high and low temperature impact resistance, and UV resistance decreased;

[0120] Comparative Example 4: In the case where the titanium dioxide / polymer molecular brush is replaced with a nano-titanium dioxide / polyhydroxy compound / organosilicon quaternary ammonium salt composite of equal mass, the water rolling angle of the obtained photovoltaic tempered glass is significantly increased, and super-hydrophobicity cannot be achieved, and the light transmittance and UV resistance are decreased;

[0121] Comparative Examples 5 and 6, which use titanium dioxide / polymer molecular brushes or silicon dioxide / tetrapod-shaped zinc oxide whiskers / alkyl phosphates alone, cannot achieve superhydrophobicity, and their UV resistance is significantly reduced.

[0122] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A photovoltaic tempered glass, characterized in that: The invention comprises tempered glass and protective coating from bottom to top; the raw materials of the protective coating, by weight, comprise: 20-45 parts of fluorine-containing polysiloxane, 10-18 parts of tetraethyl orthosilicate, 10-20 parts of silicon dioxide / tetra-needle zinc oxide whisker / alkyl phosphate, 10-20 parts of titanium dioxide / polymer molecular brush, 0.5-1 part of catalyst and 80-120 parts of solvent; the fluorine-containing polysiloxane is obtained by reacting octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and trifluoropropylmethylcyclotrisiloxane.

2. The photovoltaic tempered glass according to claim 1, characterized in that: The preparation method of the fluorine-containing polysiloxane comprises the following steps: in a nitrogen protective atmosphere, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and trifluoropropylmethylcyclotrisiloxane are uniformly mixed, stirred for reaction, tetramethylammonium hydroxide aqueous solution and water are added, stirring for reaction is continued, the pressure is reduced, and the reaction is continued to obtain the fluorine-containing polysiloxane.

3. The photovoltaic tempered glass according to claim 2, characterized in that: The mass ratio of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and trifluoropropylmethylcyclotrisiloxane is (1-2): (1.5-2): (3-5).

4. The photovoltaic tempered glass according to claim 3, characterized in that: The preparation method of the fluorine-containing polysiloxane comprises the following steps: in a nitrogen protective atmosphere, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and trifluoropropylmethylcyclotrisiloxane are uniformly mixed, stirring and reacting for 30-40 minutes at 80-90° C., heating to 110-120° C., adding tetramethylammonium hydroxide aqueous solution and water, stirring and reacting for 3-4 hours, heating to 150° C., stirring and reacting for 3-4 hours, reducing the pressure to 2-2.5 KPa, and reacting for 3-4 hours to obtain the fluorine-containing polysiloxane.

5. The photovoltaic tempered glass according to claim 4, characterized in that: The preparation method of silicon dioxide / tetrapod-shaped zinc oxide whisker / alkyl phosphate comprises the following steps: (1) uniformly mixing tetrapod-shaped zinc oxide whiskers and ethanol aqueous solution, adding ammonia water and ethyl orthosilicate dropwise, ultrasonically reacting, washing, filtering and drying to obtain silica / tetrapod-shaped zinc oxide whiskers; (2) The silica / tetrapod-shaped zinc oxide whisker and the alkyl phosphate salt solution are uniformly mixed, subjected to ultrasonic reaction, washed, filtered and dried to obtain the silica / tetrapod-shaped zinc oxide whisker / alkyl phosphate.

6. The photovoltaic tempered glass according to claim 5, characterized in that: The mass ratio of the tetrapod-shaped zinc oxide whiskers, ethanol aqueous solution, ammonia water and tetraethyl orthosilicate in step (1) is 1: (20-30): (1-1.2): (0.9-1.2).

7. The photovoltaic tempered glass according to claim 6, characterized in that: The phosphate salt solution in step (2) is an aqueous solution of potassium dodecyl phosphate.

8. The photovoltaic tempered glass according to claim 7, characterized in that: The method for preparing the titanium dioxide / polymer molecular brush comprises the following steps: S1, mixing nano titanium dioxide, polyol and ethanol aqueous solution uniformly, ultrasonically treating, washing, filtering and drying to obtain a nano titanium dioxide / polyol composite; S2, mixing the nano titanium dioxide / polyhydroxy compound complex, organosilicon quaternary ammonium salt, and ethanol aqueous solution, adjusting the pH to 3-4, ultrasonically treating, washing, filtering, and drying to obtain the nano titanium dioxide / polyhydroxy compound / organosilicon quaternary ammonium salt complex; S3, mixing nano titanium dioxide / polyhydroxy compound / organosilicon quaternary ammonium salt complex, polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt and chloroform evenly, reacting, washing, filtering and drying to obtain titanium dioxide / polymer molecular brush.

9. The photovoltaic tempered glass according to claim 8, characterized in that: In step S2, the mass ratio of the nano-titanium dioxide / polyhydroxy compound complex, organosilicon quaternary ammonium salt, and ethanol aqueous solution is 1: (0.4-0.6): (15-25); in step S3, the mass ratio of the nano-titanium dioxide / polyhydroxy compound / organosilicon quaternary ammonium salt complex, polyethylene glycol 4-nonylphenyl-3-sulfopropyl ether potassium salt, and chloroform is 1: (1.5-2): (10-20).

10. The method for preparing photovoltaic tempered glass according to any one of claims 1 to 9, characterized in that: The following steps are involved: The tetraethyl orthosilicate and the solvent are mixed and stirred, a catalyst is added during the stirring process, the pH is adjusted to 4.5, and the mixture is allowed to stand for aging to obtain silica sol; the silica sol, fluorinated polysiloxane, silicon dioxide / tetra-needle zinc oxide whisker / alkyl phosphate, and titanium dioxide / polymer molecular brush are mixed and stirred evenly to obtain a protective coating; the protective coating is applied on the surface of the tempered glass, and the photovoltaic tempered glass is obtained by curing the coating.

Citation Information

Patent Citations

  • A photovoltaic glass panel surface anti-attenuation coating and its preparation method

    CN107163783B

  • Self-cleaning photovoltaic glass coating and preparation method thereof

    CN117777847A

  • High-transmittance photovoltaic glass and preparation method thereof

    CN118026541A

Cited By

  • Nano protective coating based on water-based paint and production process thereof

    CN120248748A

  • A nano-protective coating based on water-based paint and its production process

    CN120248748B